Integration quality, value co-creation and resilience in logistics service supply chains: moderating role of digital technology. Issue 2 (30th December 2020) - Ju, Yingjie; Hou, Hanping; Yang, Jianliang
Abstract : Purpose: Using the logistics service supply chain (LSSC) as a research object, this study focuses on the relationship between integration quality (IQ), value co-creation (VCC), and LSSC resilience. Moreover, it discusses the moderating role of digital technology (DT). Design/methodology/approach: Based on data about China, this study used the structural equation model to test the research hypothesis. To verify the validity of each construct, this study used various established scales in the literature to conduct exploratory and confirmatory analysis. Findings: The results show that IQ is an essential antecedent variable that promotes VCC and LSSC resilience. Moreover, this study confirms that DT has a positive moderating effect on the relationship between IQ, VCC, and resilience. Originality/value: This study constructs a research framework to examine LSSC resilience and expands the theoretical research on the VCC theory in the supply chain literature. Moreover, this paper studies supply chain integration from a new perspective, that is, IQ, which is more in line with the reality of LSSC.